Ophthalmic complications during the dengue epidemic in Reunion Island in 2020: a case series and review of the literature - Digé Mbu-Nyamsi; Muriel Vincent; Mariane Perez-Fontana; Anne-Laurence Best; Charles Mesnard; Fréderic Villeroy; Aurélie Foucher; Loic Raffray; Cécile Saint-Pastou Terrier; Antoine Bertolotti (BMC Infectious Diseases, 2023)
Abstract Introduction Dengue is an arboviral disease transmitted by the dengue virus, whose vectors are Aedes aegypti and Aedes albopictus. The acute phase with its cohort of well-known symptoms is usually spontaneously favorable. Since 2020 in Reunion Island, a new symptom has appeared: the ocular damage of dengue fever, which has already been described in South Asia and South-East Asia. We therefore decided to describe the clinical, biological, ophthalmological, therapeutic, and outcomes of patients with ocular manifestations during dengue fever in Reunion Island in 2020. Patients and methods This was a retrospective observational study. Patients were included from January 2020 to August 2020 and then reassessed by teleconsultation 1 year later. The patients were identified from the French public health surveillance network by all ophthalmologists on the island. Medical data were collected directly from medical records. Results Twenty-eight patients were included. The mean age was 41.9 years. Ocular involvement occurred approximately 9.2 days after the onset of dengue symptoms. The main symptoms were scotoma (71.4%) and sudden decrease of visual acuity (39.2%). Eighteen patients (64.2%) had macular involvement. Fourteen patients were treated with oral or intravenous corticosteroids. Twenty-two (78.5%) patients were evaluated by telephone one year later. Scotoma and decreased visual acuity persisted in 15 patients. Thirteen patients (59%) were bothered by night driving, 32% of patients had reading difficulties and 27% of patients became sensitive to prolonged exposure to screens. Conclusion Ocular complications of dengue require early and collegial management to limit the risk of long-term sequelae. Further studies on the characteristics and complications of dengue fever are needed to better understand this disease.